2016
DOI: 10.1080/02726351.2016.1194347
|View full text |Cite
|
Sign up to set email alerts
|

The effects of powder filling on the kinetic breakage parameters of natural amorphous silica

Abstract: In this study, the effects of powder filling were investigated on the natural amorphous silica at batch grinding conditions based on a kinetic model. For this purpose, firstly eight different mono-size fractions were carried out between 1.7 and 0.106 mm formed by a 2 sieve series.Then, Si and Bi,j equations were determined from the size distributions at different grinding times, and the model parameters (Si, aT, , , j and ) were compared for four different powder fillings (5, 10, 15 and 20%). Finally, mod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 10 publications
0
4
0
Order By: Relevance
“…However, further addition of material results in lower breakage rates because the collision zones are already saturated, thus increasing the cushioning effect. On the contrary, in another study involving natural amorphous silica, Deniz [48] found that the lower the material filling in the mill, the higher is the breakage rate.…”
Section: Resultsmentioning
confidence: 89%
“…However, further addition of material results in lower breakage rates because the collision zones are already saturated, thus increasing the cushioning effect. On the contrary, in another study involving natural amorphous silica, Deniz [48] found that the lower the material filling in the mill, the higher is the breakage rate.…”
Section: Resultsmentioning
confidence: 89%
“…Ipek (2006) found that the highest mill capacity for K-feldspar is at U=1.25, while Deniz and Onur (2002) found U = 0.4 for the pumice sample. In addition, Deniz (2011a) found about U= 1.5-2.0 for the gypsum sample, while Deniz (2017) found that the optimum value of U for the highest mill capacity for natural amorphous silica was above 166.7% (U  1.667). On the other hand, Deniz (2011b) found that a maximum of U for the diatomite sample was 1.31 for up to 0.300 mm fractional particle size.…”
Section: Verification Of the Correlations Between The Liberation Degr...mentioning
confidence: 99%
“…On the other hand,Deniz (2011b) found that a maximum of U for the diatomite sample was 1.31 for up to 0.300 mm fractional particle size. However, the optimum value for under 0.300 mm fractional size was U>1.61.Plotted against fcSi versus U for chromite ore (Fig.6), and as a result of the graphical representation, different results were found with the results from some investigators(Shoji et al, 1982;Deniz and Onur, 2002; Tangsathitkulchai, 2003;Ipek, 2006;Deniz, 2011a;Deniz, 2017). From our results, it was observed that the relationship between the increase in U value and the relative absolute rate of breakage (fcSi) varies depending on the particle size.…”
mentioning
confidence: 93%
“…The rational value of content at the achievement of maximum efficiency of dry fine grinding of gypsum fineness was found in [14]. The influence of the material contained in the fill on the process of dry grinding of silica was studied in [15]. The crushed material volume was 5, 10, 15, and 20 % of the volume of cavities between the grinding bodies.…”
Section: Literature Review and Problem Statementmentioning
confidence: 99%